Therapeutic Elastic Tapes Applied in Different Directions Over the Triceps Surae Do Not Modulate Reflex Excitability of the Soleus Muscle - Magalhães, Igor E J; Mezzarane, Rinaldo A; Carregaro, Rodrigo L (Journal of sport rehabilitation, 2021)
Elastic taping has been widely used for either to facilitate or to inhibit muscle contraction. The efficacy of elastic taping is allegedly ascribed to physiological mechanisms related to subcutaneous tissue and muscle stimulation as a result of tape tension and direction. However, the underlying mechanisms that support the use of elastic taping are still unclear. To investigate changes in electrophysiological responses after 48 hours of tape application in different directions on the calf muscles of healthy individuals. Within-subjects design. Research laboratory. Twenty-seven physically active males (age 18.0 [4.2] y, height 1.65 [0.07] m, body mass 62.3 [10.3] kg) participated. Soleus H-reflex responses were evoked through stimulation of the tibial posterior nerve with 2- to 4-second interval between stimuli (32 sweeps) for each condition (baseline: without tape; facilitation: tape applied from muscle origin to insertion; inhibition: tape applied from muscle insertion to origin). The H-reflex amplitude values were normalized by the maximal direct response (Mmax). Parameters were estimated from a sigmoidal fit of the H-reflex recruitment curve (ascending limb). No significant differences were found for the parameters derived from the recruitment curve of the H-reflex among the conditions (P > .05). The authors' findings showed that, irrespective of the direction of tape application, the elastic tape applied over the triceps surae does not generate any significant alteration on the excitability of the reflex pathway for different subpopulations of motor units. The authors therefore suggest a re-examination of the current recommendations on taping direction in clinical and sports activities.